Pengaruh Strategic Leadership Terhadap Competitive Advantage Melalui Intellectual Capital Sebagai Variabel Intervening Pada Perusahaan Non-Manufaktur Terbuka di Kota Surabaya - Wardaya, Eric Wibisono (Business Accounting Review, 2016)
This study is accomplished to reveal the influence of strategic leadership to competitive advantage through intellectual capital as intervening variable in go public non-manufacturing company located in Surabaya. Competitive advantage is one of the most important variables that can determine the capabilities of the companies. Other variable like strategic leadership also contributes on creating competitive advantage. On the other hand, the application of strategic leadership cannot be separated from the support of intellectual capital in the companies.The data analysis technique used in this study was partial least square to describe the relationship among variables. The result of this study showed that strategic leadership and intellectual capital affected competitive advantage positively and significantly in go public non-manufacturer companies located in Surabaya.